La imagen de Dios y la razon social inacabada - Arroyo Aquilar, Sabino (2005)
this is a on the controversial ideological debateof postmodernity, based on the idea og God and religious culture, where the universal pretense of hermeneutics is specified, with forms of metadiscourse linked to the culture of power and the carácter of scientific and historical particularism in opposition to universality. the autor then deals with the intent or apparent decostruccion of modernity which ends in its defense, with the idea of that acquire importance since they pretend to replace waning nationalist political discourses.